Diaphragmatic Eventration Misdiagnosed as Diaphragmatic Hernia in a Preterm Infant with Respiratory Distress: A Case Report and Review of Diagnosis and Management - John Bishara; Sathyaprasad Burjonrappa; Melodi Pirzada; Claudia Halaby (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2015)
Introduction: Eventration of diaphragm is a congenital anomaly that results from a failure of muscular development of part or all of the hemidiaphragm. Clinically, eventration of diaphragm refers to an abnormal elevation of an intact diaphragm. In some cases, it may be difficult to distinguish it from congenital diaphragmatic hernia (CDH). Case Presentation: A three-week-old male, born prematurely at 30 weeks GA, who was weaned off respiratory support on the first DOL, developed respiratory distress. A chest X-ray obtained at that time when compared with the one from DOL#1 showed a new right lower lobe (RLL) opacity, suggestive of lobar atelectasis. Chest MRI revealed the "atelectatic" RLL to be the liver, raising the suspicion for CDH. Thoracoscopic evaluation revealed instead a diaphragmatic eventration, for which a plication procedure was performed. Discussion: Respiratory distress is the most common clinical manifestation of CDH and diaphragmatic eventration. As in the case of CDH, diaphragmatic eventration can be associated with various degrees of pulmonary hypoplasia due to the compression of the developing lung by the abdominal viscera. The degree of pulmonary hypoplasia and respiratory distress vary depending upon the size of the defect. Patients may be asymptomatic with small localized defects, whereas large defects in neonates can cause respiratory distress. Conclusion: Symptoms of diaphragmatic eventration can be misleading, becoming a diagnostic dilemma despite a proper evaluation. Eventration must be considered in the differential diagnosis of a newborn with respiratory symptoms and a new CXR image suggestive of lower lobe infiltrate.